(untitled) (Research, Society and Development, 2020)
Objective: To reflect the Fake News about COVID-19 and its implications to the person with Diabetes Mellitus. Method: This is a reflexive analysis carried out in discussions between teachers and students, during the meetings of the subject Topics of Philosophy of Science in Nursing and Health, in which the main principles of the philosophy and its relationship, contribution and importance in the practice of nursing were discussed. Results and discussion: It is recommended that people with diabetes seek information on official sites, because it is relevant for the population to be informed about all information related to COVID-19, in addition, the competent agencies should intensify the recommendations of social isolation and non-pharmacological measures. Conclusion: However, it is necessary to contribute to the non propagation of fake news by notifying them on the site of the Ministry of Health.